Longer Concentric Action Increases Muscle Activation and Neuromuscular Fatigue Responses in Protocols Equalized by Repetition Duration. Issue 6 (June 2019) - Lacerda, Lucas T.; Costa, Cinara G.; Lima, Fernando V.; Martins-Costa, Hugo C.; Diniz, Rodrigo C.R.; Andrade, André G.P.; Peixoto, Gustavo H.C.; Bemben, Michael G.; Chagas, Mauro H.
Abstract : Abstract: Lacerda, LT, Costa, CG, Lima, FV, Martins-Costa, HC, Diniz, RCR, Andrade, AGP, Peixoto, GHC, Bemben, MG, and Chagas, MH. Longer concentric action increases muscle activation and neuromuscular fatigue responses in protocols equalized by repetition duration. J Strength Cond Res 33(6): 1629–1639, 2019—The aim of this study was to investigate the impact of protocols equalized by the repetition duration but composed of different concentric (CON) and eccentric (ECC) durations on muscle activation and neuromuscular fatigue. Seventeen males with previous experience in resistance training performed 3 training protocols (A — 2 second CON: 4 second ECC; B — 3 second CON: 3 second ECC; and C — 4 second CON: 2 second ECC) with the Smith machine bench press exercise, all with 3 sets, 6 repetitions, 3 minutes' rest, and 60% of 1RM. The normalized root mean square of the electromyographic signal (EMGRMS ) and mean frequency electromyography (EMGMF ) for pectoralis major and triceps brachii muscles were calculated for second and fifth repetitions in each set. The results showed an EMGMF decrease across the repetitions accompanied by a progressive increase of the EMGRMS across the repetitions for all protocols and muscles. The EMGRMS was higher in protocol C when compared with protocol A and B for pectoralis major. The EMGMF was lower in protocols B and C than in protocol A for pectoralis major throughout the sets and repetitions. A higher EMGRMS and a lower EMGMF were observed in protocols B and C compared with protocol A for triceps brachii, solely in the fifth repetition. In conclusion, training protocols conducted with the same repetition duration, but with different concentric and eccentric durations, produce distinct muscle activation and neuromuscular fatigue responses, in which performing longer concentric durations could be the more appropriate strategy to increase muscle activation and neuromuscular fatigue.